Case Report: Multifocal EBV-Associated Diffuse Large B-Cell Lymphoma in a Patient With 6-MP Associated Lymphopenia With TPMT Deficiency - Müller-Scholden, Lara; Deinlein, Frank; Eyrich, Matthias; Schlegel, Paul Gerhardt; Wiegering, Verena; Wölfl, Matthias (Frontiers in Pediatrics, 2022)
Introduction: EBV associated lymphoproliferative disorders (EBV LPD) are a known complication following solid organ or hematopoietic stem cell transplantation. The disturbance of the immune system leads to a lack of control of latent EBV-infected B-cells, as control by T-cells is mandatory to prevent uninhibited cell proliferation. EBV LPD in other settings is less frequent and etiology and pathogenesis are not completely understood. Case presentation: We present the case of an 18-year old adolescent suffering from lymphoblastic T-cell lymphoma who developed a life-threatening EBV associated B-cell lymphoma while he was under therapy with 6-MP (6- mercaptopurine). An underlying homozygous TPMT (thiopurine S-methyltransferase) deficiency with subsequent insufficient degradation of 6-MP was identified as contributory for the development of a distinct lymphopenia leading to EBV LPD. The patient was successfully treated by discontinuation of 6-MP and initiating rituximab monotherapy.. Discussion: Rare cases of EBV LPD during therapy with 6-MP are reported in patients with leukemia, but no data about TPMT pharmacogenomics are available. In contrast the disease development in the presented case may be explained by the iatrogenic immunosuppression in the context of TPMT deficiency. While using 6-MP testing of genetic variations is not required for every protocol, although the use of thiopurines in patients with TPMT deficiency can cause severe immunosuppression. Our case suggests that insufficient degradation of 6-MP can have significant consequences despite dose reduction. Conclusion: When using thiopurines, TPMT genetics should be initiated and strict drug monitoring and dose adjusting must be performed by a specialized center